2015
DOI: 10.5336/medsci.2014-42236
|View full text |Cite
|
Sign up to set email alerts
|

How Familiar are Internists with a Potentially Deadly Orphan Disease?: Hereditary Angioedema

Abstract: H ereditary angioedema (HAE) is a rare but serious genetic disorder characterized by angioedema attacks in the skin, gastrointestinal tract and upper airway that can be spontaneous or the result of var- The questionnaire included HAE-related questions as well as demographic items. R Re es su ul lt ts s: : Most doctors (93.5%) reported that they had heard of HAE, and 41.9% had followed at least one patient with HAE, however, 22% of them understood the role of C1 inhibitor in HAE, but 38.7% had no idea about HAE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, a study carried out in Turkey in 2015, by which 155 internists answered a 20-item questionnaire on HAE during the National Congress of Internal Medicine, showed that awareness about the disease was higher among younger doctors (35.9 years-old versus 45.7 years-old). 14 In that study, the average time from HAE onset of symptoms to diagnosis was 26 years. 14 …”
Section: Discussionmentioning
confidence: 87%
“…However, a study carried out in Turkey in 2015, by which 155 internists answered a 20-item questionnaire on HAE during the National Congress of Internal Medicine, showed that awareness about the disease was higher among younger doctors (35.9 years-old versus 45.7 years-old). 14 In that study, the average time from HAE onset of symptoms to diagnosis was 26 years. 14 …”
Section: Discussionmentioning
confidence: 87%
“…Keeping in mind the lack of knowledge of physicians about HAE, overdiagnosis of familial Mediterranean fever in this population should not be surprising [19]. To the best of our knowledge, this is the first study reporting the ratio of familial Mediterranean fever misdiagnosis in C1-INH-HAE patients.…”
Section: Discussionmentioning
confidence: 92%
“…The findings revealed a prevalent lack of information, particularly regarding the diagnosis of HAE and the effective management of acute attacks among emergency physicians. Many survey studies on HAE awareness among physicians exist in the literature [8,[11][12][13][14]. However, to the best of our knowledge, no specific study was conducted, especially among emergency physicians.…”
Section: Discussionmentioning
confidence: 99%